Joukkoistaminen kyberrikostutkinnassa - Turunen, Olli Ilmari (2024)
Research question in this master's thesis is that whether crowdsourcing would be possible or viable as a mode of operation in cybercrime pre-trial investigation in Finland. Cybercrime investigation is known to depend on expert knowledge, acquisition of which has proven difficult for investigation authorities. Crowdsourcing, on the other hand, has increased in popularity as a means of carrying out tasks that require expert knowledge among other uses. This thesis does not aim to explore practical solutions for crowdsourcing, but to study its general feasibility in a setting that is strictly regulated and includes an executive authority. It consists of a literature review, interview study and a summary jurisdiction analysis. The literature review focuses on the ontology and typologies of crowdsourcing and summarizes related studies. The interview analysis was carried out in Finnish National Bureau of Investigation's Cybercrime Center as an expert interview analysis (n=4), where the goal was finding direct answers to the research question. A content analysis of interview results was then cross-examined and supplemented by study-ing relevant legislation. No fundamental impediment preventing usability of crowdsourcing in cybercrime investigation was found. Furthermore, it was found that there would be operational and developmental uses for crowdsourcing. On the other hand, several ethical problems, legal restrictions and investigative risks were identified. It was found that consideration of these would require rigorous planning as well as risk and impact analyses. Suitable uses for crowdsourcing in cybercrime investigation were compared with a governmental crowdsourcing typology suggested in literature. It was evaluated, that two of the most viable branches of crowdsourcing would be open public crowdsourcing and restricted expert-only crowdsourcing. The thesis adds to the general understanding of possibilities of crowdsourcing, answers directly to the question of its feasibility and opens the way for new, more specific research questions on the subject matter.